PENERAPAN SISTEM PAKAR UNTUK MENDETEKSI PENDARAHAN PADA MASA KEHAMILAN (Jurnal Pilar Nusa Mandiri, 2014)
The mortality rate due to births in Indonesia is quite high. One of the biggest complications in pregnancy is bleeding. This is due to the lack of information to pregnant women about the symptoms appear bleeding during pregnancy. Therefore, the need for a system that can help to diagnose the occurrence of bleeding (abortion) in pregnant women based on the symptoms that can be felt that abortion can be prevented as early as possible. The method used in the development of expert systems is divided into two stages: expert knowledge representation and systems development. Development experts conducted to generate a knowledge base of experts in the domain of bleeding problems that occur in pregnancy. Facts or information gathered from five specialist obstetrics and gynecology at the Police Hospitals TK. I R.Said Sukanto. The data obtained from the questionnaire results of five hospital doctors. Bhayangkara kindergarten. IR.Said Sukanto processed with SPSS software with correlation analysis method, wherein the method is to explain the relationship between variables with other variables. Data valid expert questionnaire results converted into a decision table and decision tree using reverse chronological inference method (backward chaining). Based on knowledge representation, expert systems development is then performed using the waterfall model (waterfall), which consists of three stages: analysis and requirements definition, system and software design, implementation and testing of the system. The resulting output diagnostic expert system bleeding during pregnancy is considered quite accurate with 100% precision analysis that can help pregnant women to know the symptoms of bleeding and reduce the number of bleeding during pregnancy.
Keywords: Sistem Pakar; Expert Systems; Deteksi Pendaharaan; Masa Kehamilan